Living (stained) deep-sea foraminifera from the Sea of Marmara: A preliminary study. (July 2018) - Fontanier, C.; Dissard, D.; Ruffine, L.; Mamo, B.; Ponzevera, E.; Pelleter, E.; Baudin, F.; Roubi, A.; Chéron, S.; Boissier, A.; Gayet, N.; Bermell-Fleury, S.; et al.
Abstract: In this preliminary study, we investigate living (stained) foraminifera from the Sea of Marmara. We focus on the faunal composition and geochemical signatures (trace elements, carbon and oxygen stable isotopes) in foraminiferal tests at two deep-sea sites (329 and 1240 m depth respectively). Documented by ROV observations and sampling, both study areas are heterogeneous (including bacterial mats and carbonate concretions), proximal to cold seeps and consist of dysoxic bottom water (O2 < 20 µmol/L). The prevailing dysoxia at both study areas restricts foraminiferal diversity to very low values (S < 9, H' < 0.97). Stress-tolerant species Bolivina vadescens and Globobulimina affinis dominate living faunas at both sites. The highest foraminiferal standing stock is recorded at the shallowest site underneath a spreading bacterial mat. No benthic foraminifera from either site possess geochemical signatures of methane seepage. Our biogeochemical results show that use of foraminiferal Mn/Ca ratios as a proxy for bottom water oxygenation depends strongly on regional physiography, sedimentary processes and water column structure.